2021
DOI: 10.3390/ijerph18147661
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Access to Health Care Services and Relevance of Telemedicine during the COVID-19 Pandemic in Germany

Abstract: During the COVID-19 pandemic in Germany, non-pharmaceutical interventions were imposed to contain the spread of the virus. Based on cross-sectional waves in March, July and December 2020 of the COVID-19 Snapshot Monitoring (COSMO), the present study investigated the impact of the introduced measures on the perceived access to health care. Additionally, for the wave in December, treatment occasion as well as utilization and satisfaction regarding telemedicine were analysed. For 18–74-year-old participants requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 50 publications
(60 reference statements)
4
31
0
2
Order By: Relevance
“…On the other side, individuals may truly appreciate the fact that they can at least supplement some physician visits via telemedicine services during times of the pandemic. In sum, our findings are also in line with the previously mentioned study in Germany (and international research, e.g., [ 17 ]) conducted during the pandemic [ 7 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…On the other side, individuals may truly appreciate the fact that they can at least supplement some physician visits via telemedicine services during times of the pandemic. In sum, our findings are also in line with the previously mentioned study in Germany (and international research, e.g., [ 17 ]) conducted during the pandemic [ 7 ].…”
Section: Discussionsupporting
confidence: 93%
“…The proportion of individuals replacing physician visits by telemedicine services in Germany during the pandemic mainly confirms previous findings made by Reitzle et al (also conducted in Germany, but in December 2020) [ 7 ]. Additionally, they demonstrated that appointments were more frequently performed via telephone compared to video calls [ 7 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A study from Germany, where comparable government measures were implemented during the pandemic, observed that 13.2% ( n = 102) of the individuals requiring access to medical appointments experienced limited access to a general practitioner during the first wave in April 2020. This proportion decreased to 8.8% ( n = 76) during the second wave in December 2020 [ 17 ]. In the present study, the proportion of patients who felt higher barriers to contact their general practitioner due to COVID-19 decreased with 9.1% during the pandemic, despite persisting higher barriers to contact a general practitioner among 20.8% of the patients during the second wave.…”
Section: Discussionmentioning
confidence: 99%